Excited‐state hydrogen bond strengthening of coumarin 153 in ethanol solvent: a TDDFT study. (1st February 2016) - Xu, Jinmei; Chen, Junsheng; Dong, Shunle; Fu, Aiping; Li, Hongliang; Chu, Tianshu
Abstract : So far, coumarin dyes have been extensively studied with various means to understand their photophysical behaviors andphotochemical properties. Here, our performing time‐dependent density functional theory calculation is aimed at exploring the excited‐state hydrogen bonding dynamics of coumarin 153 (C153) in protic ethanol (EtOH) solvent. The calculated results suggest that the excited‐state hydrogen bond CO⋯HO between CO group and OH group in the C153‐EtOH complex is strengthened, and the S0 → S1 transition of the complex corresponds to the highest occupied molecular orbital (HOMO) hopping to the lowest unoccupied molecular orbital (LUMO). The excited‐state hydrogen bond strengthening has been further confirmed by its larger binding energy in the S1 state than in the S0 state. In addition, because of the formation of the hydrogen bond CO⋯HO, a red shift of about 7 nm occurs in the electronic spectra of the C153‐EtOH complex, which is in good accordance with the experiment result. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We theoretically investigate the property of the hydrogen bond of C153‐EtOH complex in the aspects of the frontier molecular orbital, optimized structures, steady‐state absorption and fluorescence spectra, and infrared vibrational spectra. The results suggest that the strengthening of C=O⋯H‐O induces a redshift of 7 nm in UV‐Vis absorption spectra and energy gap between HOMO and LUMO is deceased in C153‐EtOH complex as well as the S1 state of C153‐EtOH is a locally excited state.